Contemporary Chinese Literature - Huang, Y. author. aut Link
X, 219 p.
Keywords: This book offers a case study of four of the most influential contemporary Chinese writers and 'cultural bastards' - Duoduo, an underground 'misty' poet; Wang Shuo, a 'hooligan' writer; Zhang Chengzhi, an old 'Red Guard' and new 'cultural heretic'; and Wang Xiaobo, a chronicler of Rabelaisian modern history.